INTERACTIONAL META-DISCOURSE IN UNDERGRADUATE THESIS INTRODUCTIONS BY ENGLISH STUDENTS OF MUHAMMADIYAH UNIVERSITY OF BENGKULU - Eki Saputra; Annita Intan Putri (LPPM STKIP AL MAKSUM, 2021)
The aims of this research are at investigating the interactional meta-discourse and the most dominant interactional meta-discourse category in the background of the undergraduate thesis introductions written by English students of Muhammadiyah University of Bengkulu. This study involved thirty-three backgrounds of the undergraduate thesis introductions by English students of Muhammadiyah University of Bengkulu in 2019 academic year. This study followed the meta-discourse framework of Hyland (2009) in investigating the interactional meta-discourse in the corpus of the research. The results of this research show that five categories of interactional meta-discourse found in the in the backgrounds of the undergraduate thesis introductions written by English students of Muhammadiyah University of Bengkulu in 2019 academic year, namely 216 or 37.3% hedges, 166 or 28.6% attitude markers, 104 or 18% self-mention, 77 or 13.2% boosters, and 16 or 2.9% engagement markers. In addition, the most dominant of interactional meta-discourse category found in the backgrounds of the undergraduate thesis introductions is hedges. The findings of this research give implications for the students in order to include more frequent and vary of interactional meta-discourse in writing the backgrounds of the undergraduate thesis introductions.